2018
DOI: 10.3389/fchem.2018.00500
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence for the Substrate Channeling of Rice Allene Oxide Cyclase in Biologically Analogous Nazarov Reaction

Abstract: Allene oxide cyclase (AOC) is a key enzyme in the jasmonic acid (JA) biosynthetic pathway in plants, during which it catalyzes stereospecific conversion of 12,13(S)-epoxy-9(Z),11,15(Z)-octadecatrienoic acid (12,13-EOT) to cis(+)-12-oxophytodienoic acid. Here, rice allene oxide cyclase (OsAOC) was localized to the chloroplast and its native oligomeric structure was analyzed by gel electrophoresis in the absence and presence of a protein-crosslinking reagent. The results suggest that OsAOC exists in solution as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…JA, a major phytohormone regulating abiotic stress responses, is important in early responses to osmotic and salt stress ( Fujita et al, 2006 ; Chen et al, 2017 ) and its biosynthesis was triggered by salt in Arabidopsis ( Ishiguro et al, 2001 ; Wang et al, 2015 , 2018 ). AOC affects the rate of flux through the JA biosynthetic pathway ( Yoeun et al, 2018 ). Overexpression of TaAOC1 conferred salt tolerance in wheat ( Zhao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…JA, a major phytohormone regulating abiotic stress responses, is important in early responses to osmotic and salt stress ( Fujita et al, 2006 ; Chen et al, 2017 ) and its biosynthesis was triggered by salt in Arabidopsis ( Ishiguro et al, 2001 ; Wang et al, 2015 , 2018 ). AOC affects the rate of flux through the JA biosynthetic pathway ( Yoeun et al, 2018 ). Overexpression of TaAOC1 conferred salt tolerance in wheat ( Zhao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In T. cinerariifolium , CHS and AOC are upstream genes that are more likely to become rate-limiting factors for pyrethrins synthesis ( Figure 1A ). AOC is considered to be the first key enzyme in JA synthesis, affecting the overall biosynthesis rate ( Yoeun et al., 2018 ), and CHS is the first key enzyme in the biosynthesis of pyrethrins ( Hu et al., 2018 ). Our results demonstrated that TcbZIP60 could bind to the E-box and G-box cis-elements on the promoters of both TcCHS and TcAOC , and activated the transcription of these genes in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Related to the jasmonic acid pathway, we identified OsAlba7 (acetylation lowers binding affinity protein 7) in the qShB9 region, allene oxide cyclase ( OsAOC ) (Shimizu et al 2013 ; Yoeun et al 2018 ; Yu et al 2020 ) and TIFY10A in the qShB3-2 region, and the duplicate TIFY10B in qShB7 QTL (Ye et al 2009 ). TIFY10A and TIFY10B are part of the JASMONATE-ZIM DOMAIN ( JAZ ) gene subfamily which produces proteins that are key regulators of the jasmonate hormonal response, and these genes are responsive to wounding, abiotic stress and jasmonic acid (Shimizu et al 2013 ; Ye et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%